Economic groups, corporate networks and think tanks. The case of the Centro de Estudios Públicos in Chile - Morales-Martín, Juan Jesús (2023)
This article examines the deployment of business power in Chile in a specific space such as the think tank Centro de Estudios Públicos (CEP). According to data from the year 2021, there are 79 companies, legal entities, and individuals that made an annual donation to the institution. This number of donors motivates the main objective of this article: to analyze the corporate power structure that is interlaced around this think tank and the companies that finance it. Regarding the methodology, social network analysis has been used to identify how corporate networks are organized when companies share directors and advisors (interlocking directorates). Respecting to the results, two fundamental questions are answered: 1) which are the central companies in the corporate network of the CEP's financiers? and 2) who are the closest and intermediate directors and advisors of this net of CEP funders? The leadership of economic groups like Angelini, Matte, and Luksic in the corporate network shows how these relations are intertwined. In addition, it exhibits how 40 directors of the CEP held positions in companies that provide economic stimulus to the think tank. Finally, it is concluded about the reticular structure of the power of productive elites in Chile and their consequences related to the resilience of neoliberalism in this country.